The Protective Effect of 5-Aminosalicylic Acid against Non-Steroidal Anti-Inflammatory Drug-Induced Injury through Free Radical Scavenging in Small Intestinal Epithelial Cells - Eun Suk Jung; Hyun Joo Jang; Eun Mi Hong; Hye Li Lim; Sang Pyo Lee; Sea Hyub Kae; Jin Lee (Medicina, 2020)
Background and objectives: Non-steroidal anti-inflammatory drugs (NSAIDs) have been among the major causes of small intestinal injury in clinical practice. As such, the current study investigated the protective effect of 5-aminosalicylic acid (5-ASA) against an NSAID-induced small intestinal injury. Materials and Methods: IEC-6 cells were treated with various concentrations of indomethacin with or without 5-ASA in a serum-free medium, after which an 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Dromide (MTT) assay, a cell apoptosis assay, a caspase-3 activity assay, a reactive oxygen species (ROS) content and Superoxide dismutase 2 (SOD2) activity measurement, a Western blotting for occludin and zonula occludens-1 (ZO-1) and a wound healing assay were conducted. Results: 5-ASA ameliorated indomethacin-induced cell apoptosis and an increase in the intracellular ROS content while augmenting the indomethacin-induced suppression of SOD2 activity in IEC-6 cells. Moreover, 5-ASA reversed the indomethacin-induced attenuation of occludin and ZO-1 expression and promoted faster wound healing effects in IEC-6 cells following an indomethacin-induced injury. Conclusions: Our results suggested that 5-ASA protects small intestinal cells against an NSAID-induced small intestinal injury by scavenging free radicals. Therefore, 5-ASA could be a potential treatment for an NSAID-induced small intestinal injury.